Students' perception and challenges of learning the English subjects through online classes / Sitti Hawa Sheikh Mohammad and Stefanie Natasha Rich Joseph - Sheikh Mohammad, Sitti Hawa; Rich Joseph, Stefanie Natasha (UiTM Press, 2023)
The COVID-19 pandemic has resulted in schools and universities worldwide shifting from face-to-face learning (F2F) to Online Distance Learning (ODL), and Malaysia is no exception. However, ODL has resulted in many challenges that students and lecturers have had to go through, and teaching English is no exception. This study has three aims; to analyse the student's perception of learning the English language subjects through online classes, to identify the student's challenges in learning the English subjects, and to discuss what can be improved, as well as the directions of improvement to make learning the English language subjects through online classes easier and more accessible to all. The ninety-nine respondents in this study are students taking pre-diploma and diploma courses in UiTM Sarawak. The study implements the survey research method whereby questionnaires were distributed to pre-diploma and diploma students during week 13 and week 14 of the March-August 2021 semester via Google Form. The findings were extracted, and results were analysed. The study revealed key differences in students' perception, challenges, and improvement in making learning English language subjects through online classes easier, bearable, and accessible to all. Implications of the study are also presented and discussed.